Egypt in Roman Imperial Literature: Tacitus’ Ann. 2.59-61 - Girdvainytė, Lina (Literatūra, 2016)
The article analyses Tacitus’ account of Germanicus’ Egyptian voyage (Ann. 2.59-61) in the context of anti-Egyptian discourse met with in the Roman imperial literature. After a brief discussion of Egypt’s place in the Greek and Roman imagination, the article goes on to examine Tacitus’ use of Egypt by considering the role of Germanicus in the Egyptian setting, as well as questioning the presence of prevalent (Graeco-) Roman stereotypes in the given passage. Throughout the paper, it is argued that the use of Egypt in Tacitus’ account is far more complex than the notion of general anti-Egyptian sentiment allows, and that the Tacitean representation of Egypt does not entirely fit into the paradigm of Graeco-Roman ‘Othering’. Rather than describing Egypt for its own sake, the account is carefully and artistically arranged in order to convey Tacitus’ own anti-imperialist views, implicit in his other works, such as the Histories and Agricola.
Keywords: Egypt; Tacitus; Roman imperialism; literary representation; intertextuality